1962
DOI: 10.1111/j.2044-8279.1962.tb01769.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's Evaluations of the Characteristics of the Good Teacher

Abstract: Summary. Over 800 children from primary and secondary schools ranked items descriptive of a ‘good’ teacher in four scales. The items of each scale were representative of statements made by children in short essays about ‘A Good Teacher.’ The four scales were so organised as to sample three hypothesized areas of the good teacher's class‐room behaviour: discipline, teaching and personal qualities; and to bring together in the fourth scale these three areas for comparative evaluation. A sample of teachers and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
5

Year Published

1965
1965
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 4 publications
2
17
1
5
Order By: Relevance
“…Results indicated that justice is a valuable predictor of the students' experience of their learning environment, in accordance with Taylor's (1962) theory.…”
Section: First Research Aimsupporting
confidence: 79%
“…Results indicated that justice is a valuable predictor of the students' experience of their learning environment, in accordance with Taylor's (1962) theory.…”
Section: First Research Aimsupporting
confidence: 79%
“…Students identify justice as one of the key characteristics of a good teacher (Taylor, 1962). However, they often experience their teachers' assignment of grades, dispensing or withholding of privileges or punishments, and even the student-teacher interaction itself as unjust (Fan & Chan, 1999;Israelashvili, 1997).…”
Section: Introductionmentioning
confidence: 96%
“…Justice seems to be a valuable predictor of the students' experience of their learning environment in accordance with Taylor's (1962) theory.…”
Section: Limitations Implications and Future Directionsmentioning
confidence: 54%
“…According to this theory, in order to understand psychological processes, individual experiences should be considered alongside objective environmental conditions (Bronfenbrenner 1977). Drawing on justice psychology, the way students intuitive percept, process and evaluate their teachers' just behavior is seen as a key component of several learning-setting-specific constructs (Taylor 1962).…”
Section: Introductionmentioning
confidence: 99%